2021
DOI: 10.1093/rheumatology/keaa807
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in axial spondyloarthritis: a systematic review and meta-analysis

Abstract: Background Delay to diagnosis in axial SpA (axSpA) is longer than in many other rheumatic diseases. Prolonged delay is associate with poorer outcomes, including functional impairment and quality of life. Our aims were to describe global variation in delay to diagnosis, factors associated with delay, and delay compared with PsA. Methods We searched MEDLINE, PubMed, Embase and Web of Science using a predefined protocol. Diagnos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 27 publications
(36 reference statements)
7
57
0
1
Order By: Relevance
“…Symptom onset is commonly in early adulthood, which can be a critical time for education, career and relationships. The consequence of these disruptive symptoms on mental health is compounded by the often-significant delays to diagnosis and treatment [ 1 ]. The burden of mental health comorbidities is high, for example depression prevalence ranges from 15% to 38% depending on the screening tool and population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptom onset is commonly in early adulthood, which can be a critical time for education, career and relationships. The consequence of these disruptive symptoms on mental health is compounded by the often-significant delays to diagnosis and treatment [ 1 ]. The burden of mental health comorbidities is high, for example depression prevalence ranges from 15% to 38% depending on the screening tool and population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic delay is a significant problem in axSpA [ 1 , 2 ]. A meta-analysis of 64 studies in axSpA patients reported a pooled mean diagnostic delay of 6.7 years [ 3 ]. Delayed diagnosis in axSpA is associated with worse clinical, humanistic and economic outcomes [ 4 ], while treatment with TNF inhibitors improves clinical outcomes and radiographic progression more effectively when commenced earlier in the disease process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior uveitis is the most common extra-articular manifestation of SpA and is characterized by nongranulomatous clinical features. A well-structured screening of patients affected by NGAU could allow early diagnosis, considering that the mean diagnostic delay of SpA from symptom onset ranges from 4.9 to 6.8 years [ 15 , 16 ]. It must be taken into account that delayed diagnosis is associated with worse spinal functional impairment, greater radiographic progression, reduced response to treatment, and poorer quality of life [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%